(untitled) (Global Conference on Medical and Health Sciences, 2026)
The process of teaching English as a foreign language has changed significantly due to technological development and innovative educational approaches. However, traditional teaching methods remain valuable and effective when properly integrated into modern educational practices. This article examines the role of traditional methods in English language teaching and analyzes the possibilities of their integration with communicative and digital approaches. The study highlights the benefits of combining structured grammar instruction, translation exercises, repetition, and memorization with interactive technologies and learner-centered strategies. The integration of traditional and modern methods creates balanced instruction that supports both linguistic accuracy and communicative competence.